Lymphatic endothelial cells prime naïve CD8+ T cells into memory cells under steady-state conditions - Efthymia Vokali (Nature Portfolio, 2020)
Lymphatic endothelial cells (LECs) can cross-present antigen to naïve CD8+ T cells, but the significance of this interaction was unclear. Here the authors show that LECs directly induce CD8+ T cell differentiation with memory-like phenotypes, migration patterns and transcriptome, which can later be recalled to promote effector immunity and protection from Listeria infection.